Exploring the impact of stressful life events on quality of life: meaning making and narrative reconstruction - Lotte Kring; Evald Iversen; Bjarne Ibsen; Michael Fehsenfeld (International Journal of Qualitative Studies on Health & Well-Being)
Purpose Stressful life events have the capacity to disrupt an individual’s worldview and life goals, leading to existential questions and identity loss. The subjective perception of identity is intricately linked with quality of life (QoL), and how individuals derive meaning from these stressful life events significantly influences their well-being. This article explored the impact of stressful life events on individuals’ QoL, and examined the potential for enhancing QoL through meaning making and narrative reconstruction. Methods Qualitative interviews were conducted with 11 individuals reporting diminished QoL and analysed using thematic analysis. Results The study reveals that stressful life events confront interviewees with the vulnerability of their values in life and the limits of their control, leading them to question their own beliefs and purpose in life. Consequently, these events prompt individuals to reconstruction their narratives to adapt to new life circumstances. Conclusions The study suggests that “securing the base,” including strong social relations and security in economic and housing conditions, is a prerequisite for enhancing QoL. The insights on “the base” have profound implications for QoL. Recognizing their fundamental importance, policymakers, healthcare professionals, and social service providers can support mechanisms to enhance these foundations, improving overall well-being for individuals and communities.